Netnography redefined - Kozinets, Robert V. 1964- (SAGE, 2015)
The new edition has been expanded to include: detailed guidance for researchers on how to combine online and in-person ethnographic methods to fully explore a social phenomenon, more focus on specific kinds of social media data from sites such as Facebook and Twitter, more specific examples of how netnography can be used in different social science fields, such as media studies, sociology, anthropology, nursing, and education, a discussion of the ways in which communal and cultural social identities are constantly being transformed by combinations of traditional and social media.